2017
DOI: 10.1261/rna.059428.116
|View full text |Cite
|
Sign up to set email alerts
|

RBM24 promotes U1 snRNP recognition of the mutated 5′ splice site in theIKBKAPgene of familial dysautonomia

Abstract: The 5' splice site mutation (IVS20+6T>C) of the () gene in familial dysautonomia (FD) is at the sixth intronic nucleotide of the 5' splice site. It is known to weaken U1 snRNP recognition and result in an aberrantly spliced mRNA product in neuronal tissue, but normally spliced mRNA in other tissues. Aberrantly spliced mRNA abrogates IKK complex-associated protein (IKAP)/elongator protein 1 (ELP1) expression and results in a defect of neuronal cell development in FD. To elucidate the tissue-dependent regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 52 publications
(71 reference statements)
0
21
0
Order By: Relevance
“…Consistent with our observation, Ohe et al . recently identified an inhibitory element in this region ( 31 ). The enhancement of IKBKAP exon 20 splicing was reduced as the ASOs targeted regions farther away from the 5′ splice site.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with our observation, Ohe et al . recently identified an inhibitory element in this region ( 31 ). The enhancement of IKBKAP exon 20 splicing was reduced as the ASOs targeted regions farther away from the 5′ splice site.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Ohe et al . showed that the IVS20 +13 ∼ +29 region, which overlaps with our ASO target site, contains a splicing silencer element that enhances IKBKAP exon 20 splicing when deleted ( 31 ). Interestingly, this region also contains a binding site for RBM24, which enhances IKBKAP exon 20 inclusions in muscle cells and other tissues with high levels of RBM24 expression ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exonic and intronic sequences are in upper and lower case, respectively. The recently described intronic splicing enhancer ( 48 ) is indicated. ( B ) Co-transfection experiment of ELP1 minigenes with ExSpeU1s (Ik10–72) and modified-U7 snRNA (U7-Ik10) in Hek293T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Several potential therapies for FD have been investigated including PS [30][31][32]34 , kinetin 40,41 , tocotrienols 47,48 , and the green tea component epigallocatechin gallate 49 . Other therapy strategies are based on the FD mutation acting by altering gene splicing in the nerve system in a tissue-specific manner 25,27,[50][51][52] . We focused on PS since it is a well-studied, FDA-approved food supplement that upregulates IKAP production and has no known side effects; therefore, we sought to identify other compounds that could be used in combination with PS to benefit patients.…”
Section: Discussionmentioning
confidence: 99%